Motivation and Basic Schools in Nigeria (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This paper discussed motivation strategies and Basic school teacher’s job performance. The paper critically looked at the concept of motivation and teachers. It also focused on various strategies to motivate teachers in basic schools.  The paper used secondary data. The secondary data were obtained from online literatures and print publications. The paper concluded that prompt payment of salary and allowances, regular promotion, provision of instructional materials, infrastructure facilities, provision of conducive environment, training, commendation, praise, award and involvement of teachers in functions and decision making are some of the strategies administrators of Basic schools can adopt to motivate Basic school teachers. Based on the points identified, the paper recommended the following; Government should ensure regular training, workshops and seminars for administrators of Basic schools on the use of different motivational techniques. Administrators of Basic schools should administered motivational techniques properly in order to motivate the teachers’ to perform their jobs. Government should adopt both monetary strategies and Non-monetary strategies to improve teachers’ job performance in the schools.